The Effect of Nigella Sativa on Clinical Improvement of Laryngopharyngeal Reflux Patients - Lusia Lusia; Farokah Farokah; Rery Budiarti (Diponegoro International Medical Journal, 2020)
Background : Laryngopharyngeal Reflux (LPR) decribes as retrograde reflux from gaster into the laryngopharynx because of the premature relaxation upper esophageal sphincter. The management of LPR patients includes lifestyle and dietary arrangements, medical therapy and surgical management. Nigella sativa (NS) / black cumin  has anti-inflammatory, anti-oxidant and gastroprotective effects that are expected to provide clinical improvement in LPR patients.Objective : The purpose of this study was to determine the effectiveness of NS on the clinical improvement of LPR patients.Methods : This research is an intervention study using pre and post test design methods of 34 LPR patients in Dr. Kariadi, hospital and 2 affiliated hospital  from November 2019 - March 2020.Result : 24 patients with complete data while 10 patients were unable to evaluate RFS because of a pandemic. The treatment group (15 patients) were given  omeprazole 20 mg / 12 hours plus NS 1000 mg / 12 hours orally and control group (9 patients) were given omeprazole 20 mg / 12 hours orally and placebo. Data were tested by Shapiro Wilk test, followed by the appropriate parametric test, and Fisher's exact test. There were no differences in clinical improvement in LPR based on RSI and RFS values between groups given additional NS and groups without NS, p 0.105.Conclusion : there were no significant differences in clinical improvement between groups given additional NS and groups without NS.